Empati dan Sikap Terhadap Lingkungan dengan Perilaku Pro-Lingkungan pada Remaja Akhir - Bela Sukma Bilqisti; Mustamira Sofa Salsabila; Annisa Fitriani; Rahmad Purnama Aksir (Indonesian Psychological Research, 2023)
This study aims to determine the relationship between empathy and environmental attitudes towards the pro-environmental behavior in late adolescents. The study method used is a correlational quantitative method involving 273 late adilescents aged 18-21 years. The scale for measuring pro-environmental behavior is the General Ecologycal Scale. To measure empathy, the Basic Empathy Scale is used. The measurement of environmental attitudes variable uses the Environmetal Attitude Scale. The results of this study indicate that empathy has no relationship with pro-environmental behavior in late adolescents, while environmental attitudes have a significant relationship with pro-environmental behavior in late adolescents. Then empathy and environmental attitudes have a relationship with late adolescents pro-environmental behavior with an effective contribution of 16.5%, while the other 83.5% is ecplained by other variables not examined.